CIPP Evaluation on Japanese Language Training Apprenticeship Program at Job Training Institute (LPK) Akeno Gakuen Bawen - Anggraeni, Novia; Shofwan, Imam; Oladejo, Maruff Akinlawe (Departement of Nonformal Education, Graduate Scholl of Universitas Negeri Yogyakarta, 2023)
This study aims to describe the evaluation of Japanese language training using the CIPP Model developed by Stufflebeam, including the evaluation of context, input, process, and product at LPK Akeno Gakuen. This research uses a qualitative approach. The study participants consisted of LPK managers, 2 tutors, and 5 study residents. Data collection techniques are carried out through observation, interview, and documentation methods. Data analysis techniques include data collection, data reduction, data presentation, and conclusions. The results showed that: (1) context evaluation: the training program has been achieved in accordance with the needs of learning residents and in accordance with the objectives of the institution or learning residents. (2) input evaluation: all aspects can support the implementation of Japanese language learning. However, the need for additional Japanese language tutors and infrastructure facilities requires additional or updated classrooms that are lacking. (3) process evaluation: the components of the process in LPK run well, it's just that the aspects related to tutor activities have not been maximized. It is necessary to provide appropriate training and professional development for tutors in order to maximize learning activities in class. In addition to learning obstacles, there is a need for tutors to develop effective classroom management strategies so that the specified learning goals can be achieved. (4) product evaluation: Japanese language training at LPK Akeno Gakuen has reached all components, LPK has succeeded in equipping citizens to learn by improving their knowledge and skills in Japanese.